Doing this gives x 5x 2 0 from the first factor we

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: y + 36 = 0 ( y + 6) = 0 ( y + 6 )( y + 6 ) = 0 2 In this case we’ve got a perfect square. We broke up the square to denote that we really do have an application of the zero factor property. However, we usually don’t do that. We usually will go straight to the answer from the squared part. The solution to the equation in this case is, y = -6 We only have a single value here as opposed to the two solutions we’ve been getting to this point. We will often call this solution a double root or say that it has multiplicity of 2 because it came from a term that was squared. [Return to Problems] (d) 4m 2 - 1 = 0 As always let’s first factor the equation. 4m 2 - 1 = 0 ( 2m - 1)( 2m + 1) = 0 Now apply the zero factor property. The zero factor property tells us that, 2m - 1 = 0 2m = 1 1 m= 2 2m + 1 = 0 2 m = -1 1 m=2 OR OR OR Again, we will typically solve these in our head, but we needed to do at least one in complete detail. So we have two solutions to the equation. m= 1 2 AND m=- 1 2 [Ret...
View Full Document

Ask a homework question - tutors are online